Dispersion of particulate matter (PM10) from forest fires in Chiang Mai province, Thailand - Amnauylawjarurn T. (2014)
This research investigates the factors affecting dispersion of particulate matter (PM10) released from forest fires in Chiang Mai province during March 9-13, 2007 and 2008. Atmospheric initial and boundary conditions for this area were generated by the mesoscale model, MM5. Dispersion of the PM10 at the resolution of 1 square kilometer was performed by the air pollution model, CALPUFF. Atmospheric stability over Chiang Mai is clearly indicated by the temperature inversion and wind velocity shown on Skew-T diagrams derived from the MM5. Dispersion of the PM10 over Chiang Mai vicinity was found to depend on atmospheric stability, wind direction and velocity and its topography. The simulated PM10 concentrations in Chiang Mai were 161-401 μg/m3 during March 9 - 13, 2007 and 32 - 80 μg/m3 during March 9 - 13, 2008 consistent with the observed values. The PM10 affected areas in Chiang Mai were defined according to the concentrations of the air pollutant.